Events : the force of international law - Johns, Fleur; Joyce, Richard; Pahuja, Sundhya (Milton Park, Abingdon : Routledge Cavendish, 2011)
'A GlassHouse book.'--T.p
Includes bibliographical references and index.
Keywords: Permanent Court of International Justice; International law